2018
DOI: 10.1002/er.4004
|View full text |Cite
|
Sign up to set email alerts
|

Purified high‐sulfur coal as a fuel for direct carbon solid oxide fuel cells

Abstract: Summary The use of low‐rank coal in a clean and efficient manner is a major challenge facing the current coal technology. A high‐sulfur coal with 4.5 wt% sulfur is chosen to examine the compatibility of the pristine coal and the purified contrast with a solid oxide fuel cell (SOFC) with nickel cermet anodes. Desulfurization of the pristine coal is performed by molten caustic leaching method with a removal ratio of 80%. Analyses of the physicochemical properties of coal samples indicate that the purified coal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…The porosities of the anode and cathode were approximately 30% and 45%, respectively, measured by the Archimedes method. The setup to test the fuel cell performance was the same as that in the literature . To build the testing system, the button cell was sealed tightly onto quartz tubes by silver paste, with the cathode surface exposed to ambient air.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The porosities of the anode and cathode were approximately 30% and 45%, respectively, measured by the Archimedes method. The setup to test the fuel cell performance was the same as that in the literature . To build the testing system, the button cell was sealed tightly onto quartz tubes by silver paste, with the cathode surface exposed to ambient air.…”
Section: Methodsmentioning
confidence: 99%
“…Solid oxide electrolyte DCFCs, also called direct carbon solid oxide fuel cells (DC‐SOFCs), are the only type of DCFCs with all‐solid‐state structure . As one of the most promising types of fuel cells, SOFCs have a variety of electrode materials and configurations to suit different types of fuel . Compared with the DCFCs with molten electrolytes, DC‐SOFCs are free from the troubles of corrosion of cell components and leakage of molten matter .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,6,24,25 They have greater conversion efficiency 26 because they directly convert chemical energy to electrical energy, therefore, are seemed to be the promising alternatives energy source. 4,25,27 Solid oxide FCs are categorized on the basis of temperature in three types. Initially, SOFCs were developed that were operated at high temperatures of range 900°C to 1000°C and are called high temperature SOFCs (HT-SOFCs).…”
Section: Solid Oxide Fuel Cellmentioning
confidence: 99%
“…He reported that thermal conductivity of pure metal oxides increased slowly with rise of temperature; however, mixed metal oxides showed greater conductivity at elevated temperatures . Solid oxide FCs also known as ceramic FCs are very efficient (almost 80% efficiency), fuel flexible, reliable, free from noise pollution, and have long life . They have greater conversion efficiency because they directly convert chemical energy to electrical energy, therefore, are seemed to be the promising alternatives energy source …”
Section: Introductionmentioning
confidence: 99%